Pattern of Respiratory Diseases in Pediatric Unit of a 250 Bedded District Level General Hospital in Bangladesh - Rakshit, Sudesh Chandra; Rahman, Md Mahbubur; Hye, Mohammad Abdul; Jahangir, Ahmed Ferdous; Biswas, Palash Kumar; Raju, Emdadul Haque; Hossain, Md Iqbal; Alam, Md Khairul; Hasan, Md Manir (Journal of Current and Advance Medical Research, 2020)
Background: The morbidity and mortality of under five children due to respiratory illness still not in acceptable range in spite of multiple ongoing national programs including IMCI. Objective: The present study was intended to explore the pattern of respiratory illnesses and their hospital outcome seen in admitted children admitted with respiratory illnesses. Methodology: This present retrospective study was conducted in children up to 12 years of age admitted with acute respiratory illness in pediatric unit of 250 bedded Jashore General Hospital, Jashore, Bangladesh from February 2019 to January 2020. All children between the age limit with acute respiratory illness were included in the study. Data were collected from treatment file and admission register. Results: A total of 7,484 patients were admitted in pediatric unit. Among them 840 cases (11.2%) were admitted with respiratory illnesses and bronchopneumonia contributing the majority cases 410(48.8%), followed by bronchiolitis 190(22.6%), childhood asthma 110(13.1%), wheezy child 70(8.4%), URTI 45(5.3%), laryngomalacia 12(1.4%) and tuberculosis 3(0.4%). Males were predominant in every group. Majority of respiratory diseases were from poor socioeconomic background and found lately referred. Conclusions: In conclusion respiratory illnesses contributes to most common cause of admission in pediatric unit of district level hospital Journal of Current and Advance Medical Research 2020;7(2): 50-54